PENGARUH BELANJA MODAL DAN PENDAPATAN ASLI DAERAH ( PAD ) TERHADAP PERTUMBUHAN EKONOMI KABUPATEN BERAU: PENGARUH BELANJA MODAL DAN PENDAPATAN ASLI DAERAH ( PAD ) TERHADAP PERTUMBUHAN EKONOMI KABUPATEN BERAU - Shandy Barkah (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2025)
The aim of this research is to determine the influence of Capital Expenditures on the Economic Growth of Berau Regency, to determine the influence of Original Regional Income (PAD) on the Economic Growth of Berau Regency, to determine the influence of Capital Expenditures and Original Regional Income (PAD) on the Economic Growth of Berau Regency. This study uses a quantitative approach. Quantitative research is research that emphasizes analysis of numerical data (numbers) processed using statistical methods. The results of this research concluded that based on the results of the analysis and results of data processing calculations, the development of Berau Regency Regional Government Capital Expenditures does not always increase every year, it tends to fluctuate. The results of the test show that the Regional Original Income (PAD) variable has a positive and significant impact on Economic Growth both simultaneously, namely simultaneously and partially, namely individually. If the Regional Original Income (PAD) variable received is higher, the level of Economic Growth in Berau Regency will increase.